Effect of a knowledge-based and skills-based programme for physicians on risk of sexually transmitted reinfections among high-risk patients in China: a cluster randomised trial - Don Operario, PhD; Prof. Debin Wang, MD; Nickolas D Zaller, PhD; Mei-Fen Yang, MPH; Kathleen Blaney, MPH; Jing Cheng, MPH; Qian Hong, PhD; Prof. Hongbo Zhang, PhD; Jing Chai, MD; Gregory Szekeres; Jerome Galea, PhD; Dr Prof. Thomas J Coates, PhD (Elsevier, 2016)
Background: China is experiencing growing epidemics of HIV and sexually transmitted infections (STIs). Programmes to train physicians in China on HIV and STI knowledge, diagnosis, treatment, and risk reduction counselling can potentially reduce HIV and STI risk among high-risk patients. We aimed to assess a knowledge-based and skills-based programme for physicians in China to reduce patients' STI risk. Methods: In this cluster randomised trial, we block randomised counties in two provinces in eastern China to intervention or control groups. In the intervention group, physicians from county general hospitals participated in a structured HIV and STI training programme and received opportunities to enhance their clinical and counselling skills, whereas in the control group, physicians from county hospitals received the training after the intervention group completed final assessments. We recruited STI patients from physicians in both groups, treated baseline gonorrhoea and chlamydia infections, and assessed 9-month gonorrhoea and chlamydia reinfection as the primary outcome. Statistical comparisons between intervention and delayed-control patients used multilevel analyses to account for cluster effects at county and physician levels. Analysis was by intention to treat. This study is registered with ClinicalTrials.gov, NCT00644150. Findings: Between April 1, 2007, and Sept 1, 2008, 51 counties were randomly assigned; 27 to receive immediate intervention and 24 to receive delayed intervention. 249 physicians from the 51 county-level hospitals were enrolled, 121 physicians in the intervention group and 128 in the control group. From these physicians, we enrolled 633 and 491 patients, respectively, of whom 508 (80%) and 402 (82%) were available for reassessment at 9 months. Intervention patients at follow-up had significantly lower odds of combined gonorrhoea or chlamydia reinfection than did control patients (58/508 [11%] vs 123/402 [31%]; adjusted odds ratio 0·62 [95% CI 0·46-0·84]). Interpretation: Integrating HIV and STI training into medical education in China could be an effective strategy to reduce the country's growing HIV risk and STI epidemics. Funding: US National Institutes of Health.